Latrine Utilization and Associated Factors in Mehal Meda Town in North Shewa Zone, Amhara Region, Ethiopia, 2019. (19th June 2020) - Abebe, Ayele Mamo; Kassaw, Mesfin Wudu; Mekuria, Abinet Dagnew; Yehualshet, Sisay Shewasinad; Fenta, Endegena Abebe
Abstract : Background . Worldwide lack of sanitation is a serious health risk, affecting billions of people around the world, particularly the poor and disadvantaged of people around the world. In Sub-Saharan Africa, the number of people who defecate remains the open field 215 million. According to the 2016 Ethiopian Demographic and Health Surveys report, 56% of the rural households use unimproved toilet facilities. One in every three households in the country has no toilet facility. However, achieving real gains in increasing latrine use and quality remained as a challenge. This study was used to assess the latrine utilization and associated factors in Mehal Meda town in North Shewa zone, Amhara region, Ethiopia, 2019. Result . In this study, a total of 558 participants were included. Out of households, 509 (91.2%) utilized their latrine facility. On the other way, 503 (98.8%) households utilized latrine regularly. Significant variables that were associated to latrine utilization were the occupational status of head of households, observing feces around the compound/latrine, duration of latrine utilization, shape and structure of latrine facility, latrine status during observation, and distance between water well and latrine. According to this study, the magnitude of latrine utilization in Mehal Meda district was 91.2%. It was lower than Ethiopia national expected target of MDGs (100%). Significant variables that were associated to latrine utilization were occupational status of head of households, observing feces around the compound/latrine, shape and structure of latrine facility, latrine status during observation, and distance between water well and latrine facility. Therefore, health education about latrine utilization and its advantage should be given for community in the study area.